Asset Pricing Models : A Study of CNX Nifty 500 Index Companies - Arora, Deeksha; Gakhar, Divya Verma (Indian Journal of Finance, 2019)
The objective of the study was to explore the applicability of the widely used asset pricing models, namely, the capital asset pricing model, Fama and French three - factor model (1993), Fama and French four - factor model (2012), and Fama and French five - factor model (2015) in the Indian stock market. The study was conducted on the constituent companies of CNX Nifty 500 index for a time period of 15 years spanning from October 2001 to September 2016. The asset pricing models were examined by forming portfolios for the explanatory variables considering four variables - market capitalization, ratio of book-to-market equity, profitability, and investment using the Fama - French methodology (1993, 2015). Portfolios for dependent variable side were formulated using quintiles for each of the following variables. VIF test was conducted to check the degree of multicollinearity and the four step hierarchical multiple regression was run. It was found that the three - factor model performed better than the other asset pricing models, namely, capital asset pricing model, Fama - French four - factor model, and Fama - French five - factor model in elucidating average stock returns. Thus, the study provided a substantiation of the presence of the Fama - French three - factor model in elucidation of the variations in the stock returns. The study could be helpful in future research for a generalized asset pricing model comprising of multiple risk factors.